Diseño de patrones y estructuras para ser aplicados en productos textiles tomando como referente las plantas ornamentales urbanas de la ciudad de Ambato - Otacoma Cusicahua, José Fernando (2018)
The purpose of the present project was design a series of patterns and structures to be applied in textile products taking as reference the ornamental plants of the Atocha La Liria Botanical Garden, the objective are women aged 18 to 35 years in the city of Ambato. The need is to appreciate Ambato’s identity as Land of Flowers and Fruits through an unconventional communication media, it would help the city to revitalize its positioning inside and outside the country. Ecuador preserves a great biodiversity in flora and fauna, the richness of those ancestral roots makes it different and unique in the world. The purpose of this project is to design patterns and structures through the morphological study of urban ornamental plants in Ambato’s city. The project is developed with bibliographic and documentary research, it has got theoretical and technical knowledge on the design of patterns and structures (Lupton & Phillips, 2016), the relationship between graphic design and fashion design (Díaz, 2013), Ambato: Land of Flowers and Fruits (Flores, Salazar, Palacios & Hernández, 2017) and Atocha - La Liria Botanical Garden (Vargas, 2012); the field research determined the graphic style suitable for floral prints as well as fashion and style trends. The methods used were the critical analysis through research techniques such as the semi-structured interview, coolhunting and fashion street photography and the morphological analysis with the photographic documentation were observed and applied. The Methodology of the designer and illustrator Laura Varsky (2018) was used in the development of the project. It was used for the process of creating patterns on flat surfaces, in this case in textile materials where it proposes a series of steps manuals and technology to create and demonstrate the good use of repetition patterns. The methodology proposed by Paulina Maciel (2018) was also applied, she exhibits the botanical illustration through the application of the watercolor technique, those principles helped to create the graphic language for the proposal. As a result, a series of patterns and structures design of the native ornamental plants were elaborated, they are native of the Andean region found in Ecuador. The uvilla, the ñachag and the tilo are plants that were part of the proposal. Getting a series of patterns through a graphic system that reach the expectations and objectives. It is concluded that graphic design projects managed with a design mentality can become part of visual innovation, focusing on of concepts and specific ideas that lead to the solution of established needs.